The intermembrane space protein Erv1 of Trypanosoma brucei is essential for mitochondrial Fe-S cluster assembly and operates alone - Haindrich, Alexander C; Boudová, Michala; Vancová, Marie; Diaz, Priscila Peña; Horáková, Eva; Lukeš, Julius (Molecular and biochemical parasitology, 2017)
Sulfhydryl oxidase Erv1 is a ubiquitous and conserved protein of the mitochondrial intermembrane space that plays a role in the transport of small sulfur-containing proteins. In higher eukaryotes, Erv1 interacts with the mitochondrial import protein Mia40. However, Trypanosoma brucei lacks an obvious Mia40 homologue in its genome. Here we show by tandem affinity purification and mass spectrometry that in this excavate protist, Erv1 functions without a Mia40 homologue and most likely any other interaction partner. Down-regulation of TbErv1 caused a reduction of the mitochondrial membrane potential already within 24h to less than 50% when compared with control cells. The depletion of TbErv1 was accompanied by accumulation of trCOIV precursor, with a concomitant reduction of aconitase activity both in the cytosol and mitochondrion. Overall, TbErv1 seems to have a role in the mitochondrial translocation and Fe-S cluster assembly in the organelle.
Keywords: Protein Binding; Mitochondria; Oxidoreductases; mapování interakce mezi proteiny; Erv1; protozoální proteiny; Mass Spectrometry; oxidoreduktasy; Iron-Sulfur Proteins; Trypanosoma brucei brucei; Protein Interaction Mapping; Mitochondrion; vazba proteinů; Fe-S cluster assembly; proteiny obsahující železo a síru; hmotnostní spektrometrie; Protozoan Proteins; mitochondrie; Trypanosoma